Praktik Pilihan Rasional Perempuan Desa Pelaku UMKM di Kabupaten Kediri dalam Peningkatan Perekonomian Keluarga - Hamzah Fansuri, Moh. (Sodality: Jurnal Sosiologi Pedesaan, 2023)
This writing aims to find out and analyze the practices of village women who join MSMEs actors in the Kediri Regency in improving the family economy. It is interesting to study in-depth the gender equality and the construction that women in gender equality build as actors or drivers of these MSMEs. This study uses qualitative research methods with an interpretive approach, while the theory used is a rational choice theory. The results of this study explain that: 1) The rational choice of women MSMEs in Kediri Regency is due to awareness, encouragement, and opportunities in running the micro business by playing the role of actors and existing resources. 2) The process of forming rational choices for women MSMEs in Kediri Regency is due to a solid determination to achieve goals and the pressure of the family economy. 3) The formation of capital for MSMEs actors in Kediri Regency is in various ways: (a) providing a sales mechanism initiative, (b) building social capital, (c) establishing norms, and (d) instilling trust.